Optimalisasi Penggunaan E-learning dengan Model Delone dan McClean - Sari, Elsi Puspita; Sukardi, Sukardi; Tasrif, Elfi; Ambiyar, Ambiyar (Universitas Pendidikan Ganesha, 2020)
The University of Padang (UNP) is one of the educational institutions in implementing e-learning. This research used quantitative method. The researcher evaluated e-learning by using the information success system DeLone & McClean model. This research was expected to be able to find out the overview of UNP e-learning. Based on data analysis, it showed that respondents’ level of achievement (TCR) reached 88.07% was categorized into good. The quality of information showed that the TCR reached 87.36% was categorized into good. Service quality of TCR reached 87.76% was categorized into good. The use that TCR reached 88.24% was categorized into good. Respondents’ satisfaction showed that TCR reached 88.73% was categorized into good. The benefit of TCR reached 84.10% was categorized into good. So, e-learning of Padang University had